2001
DOI: 10.1079/bjn2001427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a low-glycaemic index–low-fat–high protein diet on the atherogenic metabolic risk profile of abdominally obese men

Abstract: It has been suggested that the current dietary recommendations (low-fat-high-carbohydrate diet) may promote the intake of sugar and highly refined starches which could have adverse effects on the metabolic risk profile. We have investigated the short-term (6-d) nutritional and metabolic effects of an ad libitum low-glycaemic index-low-fat-high-protein diet (prepared according to the Montignac method) compared with the American Heart Association (AHA) phase I diet consumed ad libitum as well as with a pair-fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
113
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(125 citation statements)
references
References 29 publications
9
113
1
1
Order By: Relevance
“…Zone) 5 diets, which have been shown in many studies of free-living individuals to be associated with impressive weight loss and improved cardiovascular risk indicators over a relatively short period of time (up to 6 months). [6][7][8][9][10][11][12][13][14][15][16] Very few data are available relating to longterm (12 months or greater) comparisons of such alternative dietary regimens 6,[17][18][19][20] and only one study has been published that compares HP, HF and the more widely recommended HC-high-fibre diet over a prolonged period. 21 We have previously reported a 6-month comparison of such diets in overweight insulin-resistant women.…”
Section: Introductionmentioning
confidence: 99%
“…Zone) 5 diets, which have been shown in many studies of free-living individuals to be associated with impressive weight loss and improved cardiovascular risk indicators over a relatively short period of time (up to 6 months). [6][7][8][9][10][11][12][13][14][15][16] Very few data are available relating to longterm (12 months or greater) comparisons of such alternative dietary regimens 6,[17][18][19][20] and only one study has been published that compares HP, HF and the more widely recommended HC-high-fibre diet over a prolonged period. 21 We have previously reported a 6-month comparison of such diets in overweight insulin-resistant women.…”
Section: Introductionmentioning
confidence: 99%
“…Replacement of some dietary carbohydrates by protein (25 % v. 12 % energy intake from protein) in an ad libitum fat-reduced diet have previously been shown to induce a greater weight loss (8?9 v. 5?1 kg) due to a lower energy intake (5000 kJ/d (1195 kcal/d) v. 6201 kJ/d (1482 kcal/ d)) (22) . Another study also confirmed these findings but, when compared with an isoenergetic high-carbohydrate diet, high-protein diets did not imply a significant difference in body weight loss (23) . It has been reported that 1 kg of weight loss translates into an energy deficit of 30?5 MJ (7300 kcal) in women (24) .…”
Section: Discussionmentioning
confidence: 71%
“…However, evidence suggests that satiety-enhancing low-energy diets, particularly those high in fibre and complex carbohydrate, can suppress hunger and the desire to eat, and increase feelings of wellbeing (95,129,130,163,164) .…”
Section: Improving Weight-management Outcomesmentioning
confidence: 99%
“…Acute food deprivation increases the reinforcing value of food (127,128) , the subjective appeal of high-energy density foods and the activation of brain reward systems in response to pictures of these (43) . Sustained, hypoenergetic diets generally produce increased reports of hunger (94,110,114,129,130) and changes in hunger in response to dieting can predict successful/unsuccessful weight maintenance (131) . Experimental studies of semistarvation demonstrate that restriction of energy intake can produce profound effects including preoccupation with food, unrelenting thoughts of food and eating, distraction and limited concentration (for example, Franklin et al (132) ).…”
Section: Psychological Effects Of Energy Restrictionmentioning
confidence: 99%